1992
DOI: 10.1213/00000539-199210000-00023
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Intravenous Regional Anesthesia

Abstract: In an attempt to reduce the dose of local anesthetic during intravenous (IV) regional anesthesia of the upper limb, we combined 100 mg of lidocaine with 0.05 mg of fentanyl and 0.5 mg of pancuronium. The study was designed in a randomized, double-blind fashion to determine the efficacy of this approach in providing analgesia and relaxation during surgery and to evaluate its safety after immediate deflation of the tourniquet following IV drug injection. Eighty unpremedicated patients, ASA physical status I or I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 0 publications
1
37
0
Order By: Relevance
“…Two of these studies looked at the use of two adjuncts in combination with LA, 6 , 7 and one study compared four separate adjuncts to control. 8 Ten studies investigated opioids [6][7][8][9][10][11][12][13][14][15] and one tramadol 1 6 (Table I). Six studies investigated non-steroidal antiinflammatory drugs (NSAIDs) 8,[17][18][19][20][21] and five clonidine 8,[22][23][24][25] (Table II).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two of these studies looked at the use of two adjuncts in combination with LA, 6 , 7 and one study compared four separate adjuncts to control. 8 Ten studies investigated opioids [6][7][8][9][10][11][12][13][14][15] and one tramadol 1 6 (Table I). Six studies investigated non-steroidal antiinflammatory drugs (NSAIDs) 8,[17][18][19][20][21] and five clonidine 8,[22][23][24][25] (Table II).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies investigated non-steroidal antiinflammatory drugs (NSAIDs) 8,[17][18][19][20][21] and five clonidine 8,[22][23][24][25] (Table II). Five studies investigated muscle relaxants, 6,7,[26][27][28] three alkalization, [29][30][31] one potassium 3 2 and two temperature 33,34 (Table III). None of the studies reported sample size estimation and power analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations